2011
DOI: 10.1115/1.4004531
|View full text |Cite
|
Sign up to set email alerts
|

Study of Flow and Convective Heat Transfer in a Simulated Scaled Up Low Emission Annular Combustor

Abstract: Modern dry low emissions (DLE) combustors are characterized by highly swirling and expanding flows that makes the convective heat load on the gas side difficult to predict and estimate. A coupled experimental–numerical study of swirling flow inside a DLE annular combustor model is used to determine the distribution of heat transfer on the liner walls. Three different Reynolds numbers are investigated in the range of 210,000–840,000 with a characteristic swirl number of 0.98. The maximum heat transfer coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…The realizable k-ε turbulence model [34] was used for the analysis of the combustor flow for Reynolds numbers up to with respect to the combustor diameter. The RNG k- turbulence model was considered initially as suggested by Patil et al [19,22] for swirling flows; however the results using the realizable k- model showed better convergence and resulted in more realistic velocity and heat transfer distributions.…”
Section: Modeling Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The realizable k-ε turbulence model [34] was used for the analysis of the combustor flow for Reynolds numbers up to with respect to the combustor diameter. The RNG k- turbulence model was considered initially as suggested by Patil et al [19,22] for swirling flows; however the results using the realizable k- model showed better convergence and resulted in more realistic velocity and heat transfer distributions.…”
Section: Modeling Methodsmentioning
confidence: 99%
“…The work of these authors included isothermal convective heat transfer measurements supplemented by numerical simulations and flow characterization using particle image velocimetry (PIV). The work by Patil et al [22] reported Nusselt numbers several times higher than those obtained from the Dittus-Boelter equation, suggesting that the correlation underestimates the convective heat loads within burners. Recent work by Andreini et al [24] and Lorenzo [25] have also experimentally and computationally studied the isothermal convective heat transfer and flow within combustors using a three swirl nozzle combustor model.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The ubiquity of fluid systems characterized by an n-periodic arrangement of identical units or by multi-periodic geometric features has spawned a great deal of analyses and simulations: flow in wavy or grooved channels [9,15,16,40] or past arrays of roughness elements and vortex generators [6], acoustics in periodic wave-guides [1], energy extraction from an buoy array [12] and, of course, flow in turbomachines [8,13,14,20,23,24,30] and combustors [5,28,29,31,38,39,45] are but a few examples that fall under this category. Not surprisingly, specific analysis and simulation techniques that efficiently address this periodicity have been developed, in particular for turbomachinery applications, typically describing blade-to-blade dynamics, aeroelastic properties, and rotor-stator interactions.…”
Section: Introductionmentioning
confidence: 99%